Night-shift work is associated with increased pain perception - Matre, Dagfinn; Knardahl, Stein; Nilsen, Kristian Bernhard (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVES ': 'The aim of the present study was to determine whether shift workers exhibit increased perception of experimentally induced pain after working night shifts. ' ' METHODS ': 'The study was a paired cross-over design with two sleep conditions, after at least two nights of habitual sleep and after two consecutive night shifts at work. Fifty-three nurses in rotating shift work participated. The sensitivity to electrically induced pain, heat pain, cold pain, pressure pain and pain inhibition was determined experimentally in each sleep condition. Sleepiness and vigilance were also assessed. ' ' RESULTS ': 'Night-shift work (NSW) increased the sensitivity to electrically induced pain and heat pain (P≤0.001). Relative to habitual sleep, electrically induced pain increased by 22.3% and heat pain increased by 26.5%. The sensitivity to cold and pressure pain did not change, changes relative to habitual sleep was <5% (P>0.5). Pain inhibition was 66.9% stronger after NSW versus after habitual sleep (P<0.001). Sleepiness (measured with the Karolinska Sleepiness Scale) increased from 4.1 after habitual sleep to 6.9 after NSW (P<0.001). Vigilance decreased after NSW, measured as a 0.03-second decrease in reaction time (P<0.005). ' ' CONCLUSIONS ': 'Changes in pain sensitivity after NSW is measurable with clinically relevant effect sizes and may be an important marker for studies comparing the physiological effects of different shift work schedules. Explanations for the differential effect on different pain modalities should be a focus for future studies.
Keywords: night shift; night work; night-shift work; nurse; pain; pain perception; rotating shift work; shift work; shift worker; sleep